Development of high efficiency high speed permanent magnet generator - Richmond, Colin (Department of Mechanical Engineering, 2020)
Renewable energy technology is steadily gaining importance in the energy market because of the limited nature of fossil fuels, as well as the political pressures to reduce carbon emissions. To ensure sustainable development, adequate and affordable energy should be made available to satisfy the demand of electric energy. The High Speed Permanent Magnet (HSPM) generator is designed and developed and is expected to deliver 10 kW output power as well as to achieve a speed of 30000 RPM, however, to achieve a compact and efficient design with lower excitation losses, magnetizing currents and rotor losses requires the HSPM generator to be operated at high rated speeds of approximately 30000 RPM. However, at high speeds these machines produce a substantial amount of heat. This makes the thermal management of these machines difficult and complicated, which leads to demagnetization and the reduction of the output power and shortens the lifetime of the critical components such as the bearings. This thesis presents the design and development of the HSPM generator. It also identifies the heat generated by means of electromagnetic, mechanical and core losses. The development of an adequate cooling system (cooling jacket) is presented to avoid hot spots in the generator and thermal damage to the magnets, resulting in demagnetization. The use of pressurized oil air particles as a lubrication method for the bearings of the generator is also considered to avoid: thermal damage and starvation at the rolling element and to address the predominant concern of effectively cooling the HSPM generator ball bearings at elevated speeds. The HSPM generator is designed and developed to operate at a maximum speed of 30000 RPM to deliver 10 kW output power and is subjected to 80~92°C temperature rise with an idle power consumption of ~2kW, enough to cause hot spots on the generator, demagnetization of the magnets and severe impact to the rolling elements of the bearings. The developed cooling jacket and the newly developed oil air mist lubrication arrangement enables the control of the temperature rise of the generator and the temperature rise at the rolling element, respectively. A steady state analysis was also carried out at motor maximum power output to determine its safe operation with the objective of finding an optimal operating condition by performing a parametric study on the effect of cooling. A 3D steady state model of a 10-kW electric permanent magnet machine was generated and investigated with one cooling jacket layout. The end windings and bearings were not considered to simplify the motor model. Numerical analysis is performed with two different coolant flow rates, no flow and maximum flow (3.5 m3 /h) with special emphasis on the maximum motor temperature. The analytical calculations for the role of coolant flowrate on heat transfer characteristics for a high speed generator, showed that the convection heat transfer coefficient increases with an increase in flowrate (0.3 – 3.5 m3 /hr), while the numerical simulations showed that the maximum coolant flowrate conditions achieved lower temperature generation (27.9°C at the front bearing) throughout the generator compared to no coolant flowrate (43.7°C at the front bearing). The detailed understanding of the effects of these parameters on the generator’s temperature field will help in validating the performance of the generator with actual results.